Cross-linked chitosan with a dicationic ionic liquid as a recyclable biopolymer-supported catalyst for cycloaddition of carbon dioxide with epoxides into cyclic carbonates. (6th December 2017) - Taheri, Masoud; Ghiaci, Mehran; Shchukarev, Andrey
Abstract : A dicationc ionic liquid was synthesized and immobilized on chitosan as a catalyst for cycloaddition of CO2 with epoxides for synthesis of cyclic carbonates. Abstract : Development of eco-friendly, desirable and reusable catalysts particularly for reactions in regard to carbon dioxide fixation is still attractive in academic and industrial sectors. In this study, a dicationic ionic liquid was anchored to a cheap biopolymer, i.e., chitosan and the prepared hybrid composite was used in the cycloaddition reaction of CO2 with various epoxides for preparing five-membered cyclic carbonates under solvent-free conditions in high yield and selectivity without the addition any metal co-catalyst. The catalyst was characterized by 1 H and 13 C NMR, FTIR, UV-vis, XPS, TG, FESEM, and BET techniques. The catalyst was recovered and recycled at least five times without losing its activity and selectivity. Moreover, it has been demonstrated that chitosan through hydrogen bonding, coordination of amine groups with CO2 and also loosely bonded bromide ion to imidazolium ion have synergistic effects on the yield and selectivity of cyclic carbonates under optimum conditions. On the basis of the obtained results, a feasible mechanism was proposed for the reaction.